Decomposition of productivity growth of the Malaysian palm oil mill sector - Abdullah, Norhidayu; Hassan, Azman; Abdullah, Ramli; Ismail, Azman; Che Dir, Nur Asmani (Malaysian Palm Oil Board, 2014)
This study investigates total factor productivity (TFP) growth in the Malaysian palm oil mill sector over the period 2005-2010, using a Stochastic Frontier Approach (SFA) model. TFP growth was decomposed into three components, namely, technical efficiency (TE), technical progress (TP) and scale components (SEC). The empirical results show that productivity growth was driven mainly by TE for all palm oil mills, followed by TP. However, a change in the scale components had a negative effect on productivity growth. Overall, the study suggests that there are opportunities to improve productivity growth in the Malaysian palm oil mill sector.